The Role of Venture Capital on Start-up Business Development in Indonesia - Meita Clara Wijaya Rosa; Eko Ganis Sukoharsono; Erwin Saraswati (Journal of Accounting and Investment, 2019)
This research aimed to determine the criteria used by venture capital before investing in start-up companies, and the role of venture capital as a supporter of the start-up companies in Indonesia. This research is qualitative descriptive with a case study research approach. It was conducted in the venture capital in the city of Jakarta, using interview to collect the data. The results of this research indicate that the criteria used by venture capital before carrying out the investment process are, seeing team members, the products to be offered, marketing and exit strategies. The role of venture capital is as a supporter of the start-up companies in Indonesia by helping their funding access, assisting them to grow, supporting networking activities and mentoring, and helping them to expand the market access for the start-up products.